The impact of the COVID-19 pandemic on paediatric health service use within one year after the first pandemic outbreak in New South Wales Australia - a time series analysis - Nan Hu; Natasha Nassar; Jane Shrapnel; Iain Perkes; Michael Hodgins; Fenton O'Leary; Carla Trudgett; Valsamma Eapen; Sue Woolfenden; Katherine Knight; Raghu Lingam (Elsevier, 2022)
Summary: Background: The first wave of the COVID-19 pandemic hit New South Wales (NSW) Australia in early 2020, followed by a sharp state-wide lockdown from mid-March to mid-May. After the lockdown, there had been a low level of community transmission of COVID-19 over a year. Such pandemic experiences provide unique opportunity to understand the impact of the pandemic on paediatric health service use as countries emerge from the pandemic. Methods: We examined the difference between the observed and the predicted numbers of inpatient admissions and emergency department (ED) attendances, respectively, related to chronic, acute infectious and injury conditions, for each month during the COVID-19 period (January 2020-February 2021), based on the numbers from 2016 to 2019, using records from two major paediatric hospitals in NSW. All analyses were conducted using autoregressive error models and were stratified by patient age, sex and socioeconomic status. Findings: Health service use was significantly lower than predicted for admissions and/or ED attendances related to chronic conditions, acute infections, and injury during the lockdown in 2020. Change in health service use varied by chronic conditions, from the largest decrease for respiratory conditions (40-78%) to non-significant change for cancer and mental health disorders. After the lockdown, health service use for most health conditions returned to pre-COVID-19 predicted levels. However, for mental health disorders, increased health service use persisted from June 2020 up to February 2021 by 30-55%, with higher increase among girls aged 12-17 years and those from socioeconomically advantaged areas. There was persistently lower health service use for acute infections and increased health service use for injuries. Differences by socio-demographic factors were noted for mental health disorders and injuries. Interpretation: The immediate return to pre-COVID-19 levels for most chronic conditions after the first lockdown in NSW highlights the healthcare needs for children affected by chronic conditions. Persistently lower health service use for acute infections is likely attributable to the decreased social contact. Sustained and targeted mental health support is essential to address the potentially increased demand for services among children during and beyond the pandemic. Funding: Financial Markets Foundation for Children Chair (RL, NN), NHMRC Investigator Grant (APP1197940) (NN), NHMRC Career Development fellowship (GNT1158954) (SW)